Developing writing materials based on CTL approach for Indonesian EFL learners - Sri Wahyuni (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2017)
This study aims at developing writing materials based on Contextual Teaching and Learning (CTL) approach for Indonesian EFL learners. It adapted R and D development model proposed by Borg and Gall consisting of seven steps: research and information collection, developing a preliminary product, expert validation, product revision, field-testing/try-out, revision, and final product. On the basis of preliminary research and information collections result, the preliminary product was produced by considering the seven principles of CTL approach. From the expert validation, it shows that the developed material was on good criteria and eligible to be used as the handbook or instructional materials for Writing II. However, the expert suggested revising some points on making clearer instruction, reflecting the activities to the topic/subtopic, revising the typing errors, and arranging the spacing among the sections. After revising, it is tried out to the students. The result of the try-out shows that the product was categorized on good criteria. Based on the students’ comments, the content of the product had been already complete and interesting. The provision of more than one model texts made students understand the topic more easily. Next, the various activities provided (individual, peer, and group) made the materials more interesting.